2016
DOI: 10.1123/ijspp.2015-0490
|View full text |Cite
|
Sign up to set email alerts
|

Tracking Morning Fatigue Status Across In-Season Training Weeks in Elite Soccer Players

Abstract: Purpose: To quantify the mean daily changes in training and match load and any parallel changes in indicators of morning-measured fatigue across in-season training weeks in elite soccer players. Methods: Following each training session and match, ratings of perceived exertion (s-RPE) were recorded to calculate overall session load (RPE-TL) in 29 English Premier League players from the same team. Morning ratings of fatigue, sleep quality, delayed-onset muscle soreness (DOMS), as well as sub-maximal exercise hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
121
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 126 publications
(141 citation statements)
references
References 37 publications
4
121
1
5
Order By: Relevance
“…9 The use of simple perceived ratings of wellness is an efficient and practical approach to determining the fatigue status of elite team sport athletes. [8][9][10]30 Previous observations on elite soccer players showed a moderate-to-strong significant correlation between the players perceived rating of fatigue and the previous days total high-speed-running distance (r = -.51; P < .001). 9 Furthermore, the slope of the regression model indicated that every ~400-m increase in total high-speed-running distance led to a 1-unit decrease (eg, a player may change from very poor level of fatigue to very, very poor level of fatigue after an additional ~400-m total high-speedrunning distance) in fatigue with 37% of the variance in training load explained by all the statistically significant predictors.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…9 The use of simple perceived ratings of wellness is an efficient and practical approach to determining the fatigue status of elite team sport athletes. [8][9][10]30 Previous observations on elite soccer players showed a moderate-to-strong significant correlation between the players perceived rating of fatigue and the previous days total high-speed-running distance (r = -.51; P < .001). 9 Furthermore, the slope of the regression model indicated that every ~400-m increase in total high-speed-running distance led to a 1-unit decrease (eg, a player may change from very poor level of fatigue to very, very poor level of fatigue after an additional ~400-m total high-speedrunning distance) in fatigue with 37% of the variance in training load explained by all the statistically significant predictors.…”
Section: Discussionmentioning
confidence: 99%
“…34 In the current study, only two match days were included in the sample of 17 days, consequently, the limited match exposure and training intensity may not have been sufficient to influence muscle soreness and sleep quality. In a previous study from the same population of players, match demands accounted for ~40% of total weekly load, moreover, perceived ratings of wellness were found to be lowest on the day postmatch, 10 further showing the debilitating effects of a match on fatigue status. Indeed, the average daily training load in the current study (RPE-TL 361) is considerably lower than that reported during an AFL preseason training camp (RPE-TL 746) where daily readings of muscle soreness and sleep quality were associated with changes in load.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations